Análise dos aspectos multimodais e de design na estrutura de websites educacionais: inglês para crianças de 6 a 10 anos - Simone Maria Frade (2012)
This research study aimed at developing a case study to analyze the organizational structure of educational website genre in English for children 6-10 years old considering its multimodal (KRESS; VAN LEEUWEN, 2006) and website design (WILLIAMS; TOLLET, 2001) aspects. In this study, the educational website is considered as a digital genre, which materializes in multimodal texts. Its communicative purpose is to promote the learning of thematic content incorporating the element of fun in the information through interactive activities, games, animations and visual graphics. The purpose of this qualitative and descriptive investigation was to understand the main multimodal features of the genre educational website genre and how these features work together in making meaning. The theoretical framework that allowed the analysis of the four websites selected for this study, was grounded in the visual grammar principles proposed by Kress and van Leeuwen (2006) - framing, information value, salience as well as the principles of website design considered by Williams and Tollet (2001) - proximity, alignment, contrast and repetition. The case study developed by this research showed that understanding the multimodal features of the educational website genre, consisting of modes of representation, can be an important issue to understand the potential of semiotic resources that give its unity semiotics and textual coherence. Although the results of a case study can not be generalized to other contexts and data are private to a specific situation, the phenomenon studied (educational websites) was analyzed and described in detail, which can contribute to clarify other contexts of analysis and can be the basis for further research. Keywords: